About voice of highly sensitive person (selected problems) - Stefan, Anna (Selected issues from the theory and practice of speech therapy, 2018)
“Voice is an extension of a person; reflection of their personality”. It is believed, that voice is just an action of muscles and organs, but we must remember, that it is shaped with our personality, character, temperament and emotions. Everybody has their own level of sensitivity, which is determined to some extent genetically as well as socially. High sensitivity is not bad, unless it does affect negatively on our functioning. In recent years there have been diagnosed adaptive disorders under stress, which applied to large group of patients with personality profile called “very sensitive”. Occupational voice disorders are noted as considerable social problem. It is related to the development of civilization, omnipresent stress and problems that arise from neuromuscular mechanisms within the vocal organs. Most exposed to the larynx diseases and their effects are people, who are supposed to use their voices excessively, e.g. singers, teachers, academic lecturers, radio and tv journalist, politicians, priests, lawyers. The purpose of the paper is to present characteristics of disfunction of vocal organs based on personal experiences of some very sensitive individuals. It is preceded by short consideration on emotional sensitivity, negative influence of stress, as well as by a brief description of vocal disorders.